Energy-dependent calcium sequestration activity in a Golgi apparatus fraction derived from lactating rat mammary glands - West, D.W. (Biochimica et biophysica acta, 1981)
A fraction isolated from lactating rat mammary glands was shown by marker enzyme assays to be rich in Golgi apparatus vesicles. This Golgi apparatus-rich fraction was shown to accumulate calcium in the presence of ATP but not in its absence. Other nucleoside triphosphates were only partially effective in promoting calcium transport. Mg 2+ was required for the uptake which was also temperature and pH dependent. The uptake was sustained by the use of oxalate and phosphate as intravesicular trapping agents. In the presence of 10 mM oxalate the apparent K m for calcium uptake was 0.24 μM ionized calcium. The V was 4.45 nmol calcium/min per mg protein. Preloaded calcium could be rapidly released by the addition of the ionophore A23187 indicating an intravesicular location for the sequestered ion. Addition of ethylene glycol bis( β-aminoethyl ether)- N, N′-tetraacetic acid resulted in a slower release of preaccumulated calcium, indicating the existence of one or more efflux routes by which calcium leaves the vesicles in the presence of MgATP. Ruthenium red partially inhibited the uptake but lanthanum and particularly the sulphydryl inhibitor p-hydroxymercuribenzoate were much more effective. The properties of the calcium-sequestering system in the Golgi apparatus-rich fraction were similar to those reported for other non-muscular tissues and lend support to the hypothesis that calcium is secreted into milk via the Golgi apparatus of the mammary gland secretory cell.